Evaluation Of Risk Factors and Clinical Outcome Of Accidental Gall Bladder Perforation During Laparoscopic Cholecystectomy. - Mohammed H. Aljawher; Safa Hassan Hadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Laparoscopic cholecystectomy is the gold standard procedure for symptomatic gallstone disease, yet accidental gallbladder perforation remains a frequent intraoperative complication associated with bile and gallstone spillage. Specific Background: Previous studies discussing the postoperative consequences of gallbladder perforation during laparoscopic cholecystectomy have reported inconsistent findings regarding operative and clinical outcomes. Knowledge Gap: Limited evidence has comprehensively evaluated both the predisposing risk factors and postoperative outcomes of accidental intraoperative gallbladder perforation in elective laparoscopic cholecystectomy. Aims: This study aimed to investigate the risk factors and clinical outcomes associated with accidental gallbladder perforation during laparoscopic cholecystectomy. Results: A prospective comparative observational study involving 210 patients identified that older age, male gender, higher body mass index, diabetes mellitus, ischemic heart disease, previous abdominal surgery, and acute-on-chronic cholecystitis were significantly associated with gallbladder perforation. Most perforations occurred during separation from the liver bed (75%). Patients with perforation experienced higher rates of postoperative ileus, prolonged operative time, prolonged hospital stay, port-site infection, and intra-abdominal abscess. Novelty: This study provides a comparative clinical evaluation integrating demographic characteristics, medical history, operative findings, and postoperative complications related to accidental gallbladder perforation during laparoscopic cholecystectomy. Implications: The findings emphasize the importance of identifying high-risk patients and applying meticulous surgical techniques to reduce perforation-related morbidity, prolonged hospitalization, postoperative infection, and increased healthcare burden. Highlights: • Older age, male gender, obesity, diabetes mellitus, and previous abdominal surgery were major predictors of intraoperative gallbladder perforation.• Separation of the gallbladder from the liver bed represented the most frequent stage of perforation occurrence during surgery.• Accidental perforation was associated with ileus, longer operative duration, extended hospitalization, and higher postoperative infection rates. Keywords: Acute Cholecystitis, Gallbladder Perforation, Laparoscopic Cholecystectomy, Postoperative Complications; Surgical Risk Factors